Beyond 'Blunt': A Pathophysiology-Guided Framework for Managing High-Risk Pediatric Foreign Body Ingestion - Fatmala Haningtyas; Sigit Adi Prasetyo; Rudiyuwono Raharjo (HM Publisher, 2025)
Background: Foreign body ingestion is a significant cause of pediatric morbidity. The traditional